Desenvolvimento de técnica de ressonância nuclear magnética rápida e de respiração livre em pacientes com fibrose cística - Oliveira, Marinez Josefina Casarotto de (2017)
Introduction-objective: Cystic fibrosis is the most common genetic disease in the Caucasian population. The reduction in life expectancy is due to progressive lung disease, characterized by severe changes in the pulmonary structure, more precisely, bronchiectasis and air catabolization. Computed tomography of the chest is considered the most sensitive method to monitor lung disease in cystic fibrosis. The main disadvantage is the patient's exposure to radiation. Magnetic resonance imaging of the chest, a radiation-free technique, has been introduced as an alternative to computed tomography. Magnetic resonance has been compared to computed tomography in several studies using various sequences, but none have used the combined sensing, parallel imaging, and golden-angle radial sampling technique. The aim of this study was to evaluate the combined golden-angle radial technique of magnetic resonance imaging in patients with cystic fibrosis in relation to conventional magnetic resonance imaging and computed tomography of the chest. Cystic fibrosis has been compared to computed tomography in several studies using various sequences, but none have used the combined sensing, parallel imaging, and golden-angle radial sampling technique. The aim of this study was to evaluate the combined radial-angle golden-angle technique of magnetic resonance imaging in patients with cystic fibrosis in relation to conventional magnetic resonance imaging and computed tomography of the chest. Methods: Computed tomography and magnetic resonance of the chest were performed in 29 patients with cystic fibrosis who were followed at the pediatric pulmonology outpatient clinic of the São Lucas Hospital of the Pontifical Catholic University of Rio Grande do Sul. The Cartesian K-space sampling and, after the free-breathing magnetic resonance techniques, using the Golden_Angle Radial Sparse Parallel technique. Magnetic resonance imaging and computed tomography of the chest were evaluated by two independent observers using the Helbich-Bhalla score. Intraclass correlation coefficient and Bland-Altman analysis were used to assess agreement and reproducibility in the Helbich-Bhalla severity score. No patient was sedated or used contrast medium. Results: Intraclass correlation coefficients and the Bland-Altman graphical model between the Helbich-Bhalla scores and the evaluated methods, computed tomography, magnetic resonance and free breating magnetic resonance , showed very strong correlations in all comparisons of the total scores (ICCCT -RM = 97%, ICCCT-FB-RM = 96% and ICCCT-FB-RM = 99%). The association of the Helbich-Bhalla score of both computed tomography and magnetic resonance with pulmonary function tests were significant, mainly in relation to the severity of bronchiectasis and thickening of the bronchial walls. Conclusion: This study demonstrated that the new technique of free-breathing magnetic resonance and combination of compressed sensing, parallel imaging and radial golden-angle sampling, showed a good concordance with computed tomography in the assessment of pulmonary alterations in cystic fibrosis. The combined golden-angle radial technique can be used in clinical practice to monitor fibrocystic lung disease, and demonstrates particular value for patients who can not hold their breath during the examination.